EXPLORING THE HEART OF EXCURSION TOURISM: UNVEILING ITS SIGNIFICANCE AND CHARMS - Sarvar Abdurahimov Nasrilloyevich,; Sohibjon Zokirov Narzullo o‘g‘li, (Journal of Universal Science Research, 2024)
This article explores the significance and charms of excursion tourism, shedding light on its role as a gateway to exploration, discovery, and cultural immersion. Excursion tourism, also known as sightseeing tourism, offers travelers curated experiences that highlight the essence and uniqueness of a destination through short trips or tours. Through an examination of its significance in driving destination economies, promoting cultural exchange, and preserving natural and cultural heritage, this article unveils the enduring appeal of excursion tourism to travelers around the globe.